Study on lithium extraction from brines based on LiMn2O4/Li1-xMn2O4 by electrochemical method - Zhao, Meng-Yao; Ji, Zhi-Yong; Zhang, Yong-Guang; Guo, Zhi-Yuan; Zhao, Ying-Ying; Liu, Jie; Yuan, Jun-Sheng (Electrochimica acta, 2017)
[Display omitted] •A recovery system with LiMn2O4/Li1-xMn2O4 as electrodes was used to extract lithium.•The influence sequence of coexisting ions on lithium extraction was Mg2+> Na+> Ca2+> K+.•The values of αLi-Na, αLi-Mg and αLi-Ca were more than 300, 70 and 110, respectively.•The specific energy consumption was between 18 and 19W h·mol−1. Lithium rechargeable batteries have been used for lithium extraction in recent years. Here, we report on a highly selective lithium recovery system that consists of a LiMn2O4 positive electrode, a Li1-xMn2O4 negative electrode and a monovalent selective anion-exchange membrane. The effect of potential, temperature and coexisting ions on lithium extraction were investigated in this paper, and the lithium recovery system was applied to extract lithium from brine and concentrated seawater. The extraction capacity of Li+ reached 34.31 mg· (1g LiMn2O4) −1 at 1.2V. With higher reaction rate and lower energy consumption, 25°C (room temperature) was considered as the appropriate temperature. The system still remained high selective for Li+ even in the presence of impurity ions (K+, Na+, Mg2+, Ca2+). With simulated brine and concentrated seawater as source solutions, the concentrations of Na+, Mg2+ and Ca2+ were reduced more than 300, 70 and 100 times, consuming 18–19W h per mole of lithium recovered. And the electrodes still had high separation coefficients of Li+ and Men+ (Na+, Mg2+, Ca2+) after five cycles although a slight drop was existing.